IMPLEMENTING LORA-BASED COMMUNICATION TECHNOLOGY FOR OVERHEAD LINES VIA INTERNET OF THINGS - Lingaiah, T.; Kumar, Dr. K. Kusal; Prasad, Dr.P.H. K; Naik, Bhukya Anji Babu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
This project involves using an electrical base station as a receiver, with each home near the base station containing a transmitter. The purpose of this system is to enable easy communication between the homes and the base station in case of any faults, such as over-consumption of voltage or fuse issues. The system uses Lora WAN technology for communication, which allows for low-power, long-range communication between the devices. This abstract summarizes the key components and objectives of the project, which aims to improve the reliability and efficiency of the electrical grid by enabling real-time fault detection and communication.